Corpora Amylacea in the Human Brain Exhibit Neoepitopes of a Carbohydrate Nature - Riba, Marta; Augé, Elisabet; Tena, Iraida; del Valle, Jaume; Molina-Porcel, Laura; Ximelis, Teresa; Vilaplana, Jordi; Pelegrí, Carme (Frontiers in Immunology, 2021)
Corpora amylacea (CA) in the human brain are polyglucosan bodies that accumulate residual substances originated from aging and both neurodegenerative and infectious processes. These structures, which act as waste containers, are released from the brain to the cerebrospinal fluid, reach the cervical lymph nodes via the meningeal lymphatic system and may be phagocytosed by macrophages. Recent studies indicate that CA present certain neoepitopes (NEs) that can be recognized by natural antibodies of the IgM class, and although evidence of different kinds suggests that these NEs may be formed by carbohydrate structures, their precise nature is unknown. Here, we adapted standard techniques to examine this question. We observed that the preadsorption of IgMs with specific carbohydrates has inhibitory effects on the interaction between IgMs and CA, and found that the digestion of CA proteins had no effect on this interaction. These findings point to the carbohydrate nature of the NEs located in CA. Moreover, the present study indicates that, in vitro, the binding between certain natural IgMs and certain epitopes may be interfered by certain monosaccharides. We wonder, therefore, whether these inhibitions may also occur in vivo. Further studies should now be carried out to assess the possible in vivo effect of glycemia on the reactivity of natural IgMs and, by extension, on natural immunity.